The relationship between the leadership style of the head of the room and the performance of the executive nurse at Labuang Baji Regional Hospital - Nurindasari, Sri; Suandi, Suandi (Patria Artha Journal of Nursing Science, 2024)
The relationship between the leadership style of the head of the room and the performance of the executive nurse at Labuang Baji Regional Hospital. supervised by Saputri Mulyana and Sri Nurindasari.Nurses have an important role in implementing and documenting nursing care. Nurse performance is influenced by several factors, one of which is the leadership of the head of the room. This study aims to determine the relationship between the leadership style of the head of the room and the performance of the implementing nurse at the Laburan Baji General Hospital, Makassar.The design of this research was cross sectional with a sample size of 48 nurses using purposive sampling technique. The independent variable of this research is leadership style and the dependent variable is nurse performance. Data were collected using questionnaires and observations then analyzed using Linear Regression statistical tests (p0.005).The results of the study show that 1. The leadership style of the head of the room at Laburan Baji Hospital Makassar is more dominant in applying the autocratic leadership style, which is equal to 77.08%. The performance of implementing nurses at Labuang Baji Regional Hospital in documenting nursing care is in the medium category, namely 81.25%. The leadership style of the head of the room is moderately correlated with the performance of the implementing nurse in documenting nursing care, namely (r = 0.399). It is expected that nurses can improve their performance in documenting nursing in accordance with leadership in the workplace and also the hospital organizes training related to leadership.